Exploration of chemotherapy-free regimen after multi-line chemotherapy-induced renal impairment in recurrent ovarian cancer: Case report and literature review - Zhang, Liu-ping; Yang, Xiang; Zheng, Wei; Feng, Kai-xun; Li, Hu (Frontiers in Oncology, 2023)
Introduction Platinum-based combination chemotherapy is recommended first choice for relapsed ovarian cancer. However, many of the chemotherapeutic agents are nephrotoxic and can promote kidney dysfunction, which affect the efficacy of cancer treatment and the survival of the patient. There is a need to explore long-term treatments of chemotherapy-free regimen of chronic kidney disease in recurrent ovarian cancer. Case presentation: A 41-year-old female patient was presented with stage IIIC well-differentiated ovarian serous papillary adenocarcinoma in 2009. The patient had recurrence of platinum resistance after secondary cytoreductive surgery, and it was difficult to continue chemotherapy after multiple lines of chemotherapy due to myelosuppression, renal impairment and other factors. The patient accepted Niraparib-based treatment regimen after multi-line chemotherapy-induced stage 4 chronic kidney disease. Niraparib combined with anlotinib achieved median PFS of 11 months, disease re-progression, and the patient was switched to niraparib combined with letrozole from October 2021. No evidence of tumor progression was observed till date and the renal toxicity is acceptable. Conclusions: In patients with relapsed ovarian cancer, treatment becomes increasingly challenging to subsequent therapies because of renal impairment and emerging drug resistance. Niraparib-based treatment regimen may be a good choice for patients with well-differentiated serous adenocarcinoma of the ovary who are intolerant to chemotherapy.